Needs frustration makes me silent: Workplace ostracism and newcomers' voice behavior. (September 2019) - Wu, Wen; Qu, Yongzheng; Zhang, Yihua; Hao, Shengyue; Tang, Fangcheng; Zhao, Na; Si, Haijian
Abstract: Employing self-determination theory, in this study, we explore how workplace ostracism (being ignored and excluded by others) affects newcomer's voice behavior. Through an empirical study with 353 matched supervisor–subordinate pairs from a large high-technology company, we find that workplace ostracism has negative influence on newcomer's both promotive and prohibitive voice through the mediating effect of psychological needs satisfaction. In addition, narcissism moderates the effects of ostracism on psychological needs satisfaction. Theoretical and practical implications of these findings are discussed.